2018
DOI: 10.1002/cae.22080
|View full text |Cite
|
Sign up to set email alerts
|

Robotics and kinetic design for underrepresented minority (URM) students in building education: Challenges and opportunities

Abstract: Owing to the widespread distribution of open‐source robotic software and cheaper hardware, design education in architecture and engineering is evolving to emphasize interactive and dynamic geometries, using new digital media and technologies. However, ethnic minority groups are still underrepresented in technology‐driven changes in architecture, and their career is at risk in the growing tech‐related job markets of the architecture, construction, and engineering (ACE) industry. In this context, the paper addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…As analyzed in other studies, robotics has not yet been implemented in a concrete way in education systems. However, due to the potential it offers for the academic development of students, it will probably be included in the not-too-distant future as a specific subject in various education systems [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As analyzed in other studies, robotics has not yet been implemented in a concrete way in education systems. However, due to the potential it offers for the academic development of students, it will probably be included in the not-too-distant future as a specific subject in various education systems [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the application of robotics in the educational field involves other associated factors in the education of students [25], including contributing to the development of logical thinking, psychomotor skills, and spatial perception of students [26], promoting student autonomy through the development of their own projects [27] and the active involvement of students in the teaching and learning process [28], promoting creativity, research, and understanding oriented toward the computer world [29], generating students' problem-solving skills [30], encouraging the development of students' digital competence [31], associating it with other pedagogical methods, such as project learning, collaborative learning, or cooperative learning [32], and encouraging functional learning given that it generates resources that can be applied in the social environment [33]. Therefore, it can be said that robotics in education generates a series of advantages [34], including learning to work in a team [35], increasing self-confidence [36], promoting entrepreneurship [37], developing skills [38], identifying and taking an interest in other disciplines [39], increasing concentration [40], increasing creativity [41], and promoting curiosity and increasing interest in mathematics [42].…”
Section: Introductionmentioning
confidence: 99%
“…Its basic concepts and terminology were introduced in the 1970s [17], but along with the rise of the green building industry, the adaptively movable building is once again gaining increasing popularity as an emerging paradigm in sustainable architecture and building design education. Lee et al [11] suggested simplified formulas to estimate the energy performance of movable windows, and Yi [18] discussed robotics-based design experiments as well as the educational effectiveness of introducing kinematics into design studio curriculums. In particular, the responsively acclimatized design of building enclosures, inspired by biomimicry (or biomimetics) that takes the characteristics of nature as a dominant driver for design strategies and form-making [5,9,19], is progressively studied with a high-level abstraction of natural principles, owing to the development of robotics and sensor technologies [8].…”
Section: Responsive Façade Design For Sustainable Architecturementioning
confidence: 99%
“…However, despite the active employment of robot machines and technological advancements on the engineering side of AEC [2,3,8], it is still foreign to architecture and building design, and above all, gaps in industrial development and academic education have increased in those areas. For the majority of architecture students and design tutors, technology has been perceived to be less impactful or even irrelevant to enhance the design quality and elevate academic endeavor to search for newer agendas [20]. It is found that there exist only a few architectural courses that focus on robotics, in contrast to the rapid pace of knowledge growth in the field of robotics engineering.…”
Section: Introductionmentioning
confidence: 99%
“…To do so, related knowledge from fundamental to advanced levels needs to be properly curated with the higher education system of professional architectural programs. Although the incorporation of robotics in the architectural studio has been found to be effective in increasing students' overall achievements [20], we suffer from a scarcity of reliable information about robust models of education content. Students' motivation, expected outcomes, and the representation of individual preferences remain a domain of inquiry.…”
Section: Introductionmentioning
confidence: 99%